TRANSMIGRATION IN THE UPANISHADS AND THE GREEK '[HOUGHT - Aranjaniyil, Gabriel (Journal of Dharma, 1979)
Transmigration is a belief taken for granted in Hinduism, Buddhism and Jainism, It was during the Upanishadic period that this belief arose in India. The Upanishads, during the formation of which Buddhism and Jainism arose as a reaction, to Brahmanic Hinduism, first taught this doctrine. * Among the Greeks, it was Plato who gave a significant role to this theory in his philosophy. His philosophy is close to the Upanishadic views in many ways. H